European Union after the 2014 elections to the European Parliament and its future: Implications for Poland (Economic and Political Thought, 2015)
Successive elections to the European Parliament, one of the most importantinstitutions of the European Union, took place in May 2014. Polishcitizens took part in the election for the third time. It coincided with the tenthanniversary of Poland’s accession to the European Union. Thus, it is a goodtime to sum up the effects of our presence in the group of integrated states aswell as try to analyse problems and changes that took place in the EuropeanUnion in the past decade. This is the aim of the article. Moreover, it showsthe position and role of the European Parliament in the European Union aswell as its powers, which increased when the Treaty of Lisbon entered intoforce on 1 December 2009. The article also presents the European Unionafter the elections to the European Parliament in May 2014 and its prospects,which are not so obvious nowadays. As the author writes, various seriousthreats and black clouds are gathering above the European Union.